A scoping review of inferential reading comprehension research in the present decade - Rondon, Tatiana Koerich; Neves, Patricia de Andrade (Língu@ Nostr@, 2022)
Inferential comprehension has had a notable role in reading comprehension research, with many studies investigating the process in different contexts. Several researchers have proposed models of reading comprehension where inference generation has great prominence (GAGNÉ; YEKOVICH; YEKOVICH, 1993; KINTSCH; VAN DIJK, 1978; VAN DEN BROEK et al., 1999). That said, the objective of this study was to conduct a scoping review that proposed to discover the focus of studies about inferential reading comprehension in the present decade through the Periódicos da Capes platform. This study consisted of bibliographical research (GIL, 2017), comprising a sample of twelve studies. To analyze the articles, we explored the following aspects: inference types, offline and online methods of measuring comprehension, narrative and expository text types, individual differences, and L1 and L2 research. We presented a summary and critical appraisal of each one according to the topics outlined. The results showed that English was the prevalent language investigated considering L1 and L2, most studies used offline methods to measure comprehension, and narrative texts were the most popular in inferential reading research. It was out of the scope of this study to include research with cognitively impaired participants, studies conducted in graduate courses not published in peer-reviewed journals, and articles available only on other platforms, such as Web of Science, ResearchGate, and others. Despite the limitations, this study offered insight regarding future research in inferential reading comprehension. We suggest future studies employ online and offline measures, distinguish differences in inferential processes between text types, and explore individual differences in inference generation.